Complacency of solah and its ramification on mental health - Mohamad Yusop, Yusni; Wan Othman, Wan Norhayati; Azahari, Raihanah; Mahayudin, Abdul Aziz; Zainudin, Zaida Nor (Human Resource Management Academic Research Society, 2019)
Introduction: Although the purpose of complacency among the Muslims derived from the practice of worship as prescribed by God but the issue is to what extent this appreciation has been identified. This paper aims to analyze parts of the complacency elements through obligation of solah (praying) as described in the Quran. The research questions are to investigate how often do the respondents feel about the elements of complacency on their daily prayers? And, what is the perception of respondents feeling about the elements of complacency on their daily prayers? Method: This survey study using mixed-method approach. Quantitave data was collected using questionnaire while the qualitative data was collected using interviews. Data were collected from 49 respondents aged 19 to 21 years old who is studying at the Teacher Training Institute in Selangor. A questionnaire consists of 14 item with a 5-point likert scale is set up with the reliability of Cronbach Alpha .87. The researchers identified some verses about solah from various surah in the Qur'an as a source of data acquisition to develop a questionnaire. Interviews are conducted by asking the respondents on how they perceived solah in their daily life. The data from the questionnaires were analyzed using SPSS to determine the mean and standard deviation and also thematic coding for qualitative data. Results: Data showed that most students received a high level of complacency from Solah practice. Respondents’ perceptions from the interviews also support the elements as measured consist of seeking God's help, increasing rewards, avoiding devil's interference, fearing God, blessings, guidance, zikrullah, preventing indecency and evil, promoting good deeds, and purify soul. Conclusions: The responses illustrate how complacency elements affected the respondents. The findings of this study have implications for the development of student’s mental health in their everyday life and also open the possibities of integrating solah in mental health treatment as a form of therapy.